Some Theoretical, Legal and Practical Issues on Human Rights of Aliens - Cong Giao, Vu; Duc, Nguyen Dinh (VNU Journal of Science: Legal Studies; Vol 34 No 2DO - 10.25073/2588-1167/vnuls.4151, 2018)
This paper analyzesthe concepts “alien” and “rights of aliens”, to explain the differences between “rights of citizen” and “rights of aliens”, the history of formation, development as well as content of rights of aliens in international law and Vietnam law. The authors argue that Vietnam's legislation has made strides in protecting the rights of aliens in comparision with the standards of international human rights law since the Vietnamese government published the 2013 Constitution. However, there are still gaps between the rights of foreigners and those of citizens, which has not been really improved in the context of globalization. Keywords Alien/non-citizen, rights of alien/non-citizen, rights of citizen, international human rights law, Vietnam. References   [1] Australian Human Rights Commission: Rights of non-citizens, https://www.humanrights.gov.au/rights-non-citizens . [2] General Assembly, Question of Diplomatic Asylum. Report of the Secretary-General, UNHCR, 22/9/1975. http://www.unhcr.org/protection/historical/3ae68bf10/question-diplomatic-asylum-report-secretary-general.html . [3] Geogre Gigauri, RSC Working Paper No. 31 Resolving the Liberal Paradox: Citizen Rights and Alien Rights in the United Kingdom, University of Oxford, 2006. [4] Hannah Dittmers, The Applicability of the Alien Tort Statute to Human Rights Violations by Private Corporations, Journal of Science, Humanities and Arts, University of Michigan Law School 9/6/2017. [5] Hélène Lambert, The position of aliens in relation to the european convention on human rights, Council of Europe, 2001. [6] James A. R. Nafziger, The General Admission of Aliens under International Law, The American Journal of International Law Vol. 77, No. 4 (Oct., 1983). [7] Jamin B. Raskin Legal Aliens, Local Citizens: The Historical, Constitutional and Theoretical Meanings of Alien Suffrage, 141 University of Pennylvania Law school (1993), https://scholarship.law.upenn.edu/penn_law_review/vol141/iss4/3 . [8] Kay Hailbronner, Jana Gogolin, Aliens, Max Planck Foundation for International Peace and the Rule of Law, 7/2013. [9] Lauren Carasik, The Alien Tort Statute and Human Rights Law, Foreign Affairs, https://www.foreignaffairs.com/articles/united-states/2017-10-25/alien-tort-statute-and-human-rights-law . [10] Leydet, Dominique, "Citizenship", The Stanford Encyclopedia of Philosophy (Fall 2017 Edition), Edward N. Zalta (ed.), https://plato.stanford.edu/archives/fall2017/entries/citizenship/ . [11] Office of the United Nations High Commissioner for Human Rights: The rights of Non-citizens, New York and Geneva, 2006. [12] Saroj Chhabra, Diplomatic Asylum: A Necessary Evil to the Protection of Human Rights, International Journal of Law and Legal Jurisprudence Studies Volume 4 Issue 2. [13] Vũ Công Giao, Lã Khánh Tùng, Tường Duy Kiên: Giới thiệu Công ước Quốc tế về các quyền dân sự và chính trị (ICCPR, 1966), NXB. Hồng Đức, 2012. [14] Đinh Ngọc Vượng, Dân cư trong Luật Quốc tế, Giáo trình Công pháp Quốc tế, NXB. ĐHQGHN, 2014. [15] Nguyễn Thị Thuận, Luật Hình sự Quốc tê, Giáo trình Công pháp Quốc tế, NXB. ĐHQGHN. [16] University of Minnesota Human Rights Center: Study guide, The Rights of Non-Citizens, 2003, http://hrlibrary.umn.edu/edumat/studyguides/noncitizens.html . [17] VOV, Từ ngày 1/1/2016, miễn thị thực qua lại giữa các nước ASEAN, 1/1/2016, https://vov.vn/tin-24h/tu-ngay-112016-mien-thi-thuc-qua-lai-giua-cac-nuoc-asean-464712.vov . [18] Website của Cục An ninh Quốc gia Hoa Kỳ, https://www.dhs.gov/immigration-statistics/data-standards-and-definitions/definition-terms#permanent_resident_alien .